2017
DOI: 10.1016/j.pharmthera.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and immunological targeting of tumor mesenchymalization

Abstract: Controlling the spread of carcinoma cells to distant organs is the foremost challenge in cancer treatment, as metastatic disease is generally resistant to therapy and is ultimately incurable for the majority of patients. The plasticity of tumor cell phenotype, in which the behaviors and functions of individual tumor cells differ markedly depending upon intrinsic and extrinsic factors, is now known to be a central mechanism in cancer progression. Our expanding knowledge of epithelial and mesenchymal phenotypic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 189 publications
(221 reference statements)
0
14
0
Order By: Relevance
“…In TNBC in particular, Suarez-Carmona et al (75) the recruitment of MDSCs to the tumor site. Furthermore, as described above, the reversion of mesenchymal features could render cancer cells more responsive to immune-mediated lysis (76,77), and the reduction of MDSC recruitment to the tumor site has been reported to enhance the response to vaccination (78).…”
Section: Discussionmentioning
confidence: 99%
“…In TNBC in particular, Suarez-Carmona et al (75) the recruitment of MDSCs to the tumor site. Furthermore, as described above, the reversion of mesenchymal features could render cancer cells more responsive to immune-mediated lysis (76,77), and the reduction of MDSC recruitment to the tumor site has been reported to enhance the response to vaccination (78).…”
Section: Discussionmentioning
confidence: 99%
“…EMT plays an increasingly recognized role in cancer progression and resistance to therapy (17,18). We found that the TGFbinduced EMT in EGFR/ALK-mutant and KRAS-mutant/LKB1deficient cells requires both mTORC1 and mTORC2, indicated by the activation of P-AKT and P-S6 and by the blockade of mesenchymal morphology and EMT signature proteins upon MTI-31/ AZD8055 treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Although the clinical use of the mTORC1-selective rapalog therapy (e.g., temsirolimus, everolimus) validated mTOR as a cancer target, the importance of mTORC2 in cancer therapy remains elusive. Epithelial-mesenchymal transition (EMT) is known to be important in tumor metastasis and resistance to therapy (17,18) and may involve mTORC2 (19)(20)(21). Additionally, overexpression of the mTORC2 component Rictor was observed in 66% lung adenocarcinoma brain metastases (22) and Rictor overexpression was sufficient to induce glioma formation in mice (23).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal-to-epithelial transition (MeT) is the reverse process of eMT that offers phenotypic plasticity for conversion of mesenchymal cells to epithelial derivatives (15). eMT status is closely associated with cancer metastasis, stemness, immune escape and drug resistance in HCC (17,18). It was previously identified that eMT is involved in the regulation of Pd-l1 in several cancer types, including breast cancer (19,20), lung cancer (17,21), pancreatic cancer (22), esophageal cancer (23) and salivary adenoid cystic carcinoma (24).…”
Section: Tnf-α-mediated Epithelial-to-mesenchymal Transition Regulatementioning
confidence: 99%